Modified Arthroscopic Suture Fixation of Posterior Cruciate Ligament Tibial Avulsion Fracture in the Setting of Multiligament Knee Injury in Teenager - Miguel Quesado; Ana Sofia Esteves; Nuno Vieira da Silva; Tiago Costa; Nuno Ferreira; Hélder Nogueira (Case Reports in Orthopedics)
The posterior cruciate ligament (PCL) avulsion fracture is a rare injury and occurs mainly in young patients. The development of arthroscopic techniques and fixation methods has improved the treatment of this entity. This report describes a modified arthroscopic suture fixation of a small tibial avulsion fracture of the PCL. A 17-year-old male, injured in a motorcycle crash, was admitted to the Emergency Department and diagnosed with left knee PCL tibial avulsion fracture, lateral collateral ligament (LCL) femoral avulsion fracture, and patella fracture. The PCL was fixed arthroscopically using a Knee Scorpion and two SutureTapes (Arthrex, Munich-Germany) through of an interlaced configuration at the base of the fragment using a transseptal approach and fixed distally over a cortical button on the anterior cortex. The LCL was repaired with two cannulated screws by a percutaneous approach. At 1 year of follow-up, the fragment was healed with tibiofemoral congruence, and the knee was stable with complete range of motion. The Tegner Lysholm Knee Scoring Scale (TLKSS) was 92.